When What You Know Ain’t Necessarily So: A Comparative Analysis of the Texas School Foundation Program Revenues for Independent and Charter School Districts - R. Anthony Rolle; R. Craig Wood (Educational Considerations, 2012)
Texas charter school districts (CSDs) are accredited and monitored by the Texas Education Agency (TEA) utilizing the various components within the state accountability systems for both state and federal requirements.
Keywords: Texas Public School District; funding mechanism; data analysis; equity; outcomes; Charter School Districts; revenues; recommendations